Prussian blue nano material as well as preparation method and application thereof
By dropping solution A and solution B into solution C in the preparation method in the sodium ion battery and subjecting to weak acid treatment, the problems of poor dispersion and agglomeration of Prussian blue nanomaterials were solved, and the electrochemical performance of sodium ion battery was improved.
Patent Information
- Application Number
- CN202411325550.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the application of existing Prussian blue nanomaterials in sodium ion batteries, the rapid conduction of sodium ions is unfavorable due to poor dispersion and agglomeration, resulting in a degradation of electrochemical performance.
By dropping solution A and solution B into solution C, aging and adding weak acid for surface treatment, Prussian blue nanomaterials with good dispersion and uniform size were prepared to reduce agglomeration and improve the conduction efficiency of sodium ions.
The rate charge and discharge performance and cycle stability of sodium ion batteries are improved, the discharge specific capacity is enhanced, and the electrochemical performance is optimized.
Smart Images

Figure CN119263304A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery positive electrode materials, and more specifically, to a Prussian blue nanomaterial and a preparation method and application thereof. Background Art
[0002] With the continuous progress of society, energy plays an increasingly important role in the process of human development. However, the excessive consumption of non-renewable energy such as coal, oil, and natural gas in the past few decades has caused a sharp decline in their reserves and brought about a series of environmental problems such as haze and soil pollution. Therefore, the development and utilization of new green renewable energy has attracted much attention. However, clean energy such as wind energy, tidal energy, and solar energy are subject to many restrictions of geographical factors and natural conditions, and have a certain timeliness, so people have put forward higher requirements for energy storage technology, especially electrochemical energy storage technology. In recent years, lithium-ion batteries have developed rapidly and are widely used in the fields of power batteries and electrochemical energy storage. However, due to the uneven distribution and low abundance of lithium resources in the earth's crust, the cost of lithium-ion batteries is high, which is not conducive to their large-scale application in the field of electrochemical energy storage. Relatively speaking, sodium is abundant in the earth's crust, widely distributed, and inexpensive, so sodium-ion batteries are regarded as the most promising alternative to lithium-ion batteries.
[0003] Sodium and lithium belong to the same group IA, and the working principle of ion batteries is similar, but the radius of sodium ions is larger than that of lithium ions, and it is more difficult for sodium ions to diffuse in the lattice. The volume deformation caused by the embedding and extraction process is more serious. Therefore, the electrode materials suitable for lithium-ion batteries may not be suitable for sodium-ion batteries. It is crucial to develop electrode materials that can provide rapid migration of sodium ions. Currently, the commonly used positive electrode materials for sodium-ion batteries include Prussian blue analogs, layered oxides, and polyanionic compounds. Prussian blue analogs have attracted much attention due to their open three-dimensional network framework and rich redox sites. In addition, its raw materials are easy to obtain, the synthesis conditions are mild, and it has the potential for large-scale synthesis. The liquid phase method is one of the main ways to synthesize such materials, but its large solubility product constant causes too fast crystallization during the reaction, and the nanoparticles often agglomerate, which is not conducive to the rapid conduction of sodium ions and causes a decrease in electrochemical performance. Researchers have found that adding chelating agents, surfactants, and other methods to the reaction system can inhibit the reaction rate and improve the agglomeration phenomenon to a certain extent, but the effect is relatively limited. Summary of the invention
[0004] The present application is provided to solve the above-mentioned defects existing in the prior art. A Prussian blue nanomaterial and a preparation method and application thereof are needed to solve the problem that the Prussian blue nanomaterial obtained by the current method for preparing the Prussian blue nanomaterial has poor dispersibility and agglomerates a lot, which is not conducive to the rapid conduction of sodium ions in the application of sodium ion batteries, resulting in a decrease in electrochemical performance.
[0005] In a first aspect of the present application, a method for preparing a Prussian blue nanomaterial is provided, characterized in that the preparation method comprises: solution A and solution B are respectively dropped into solution C to obtain a mixed solution, and during an aging process of the mixed solution, a weak acid is added to the aged mixed solution, and after surface treatment, a Prussian blue nanomaterial is obtained, wherein solution A comprises an iron source, a complexing agent, a reducing agent and water, solution B comprises sodium ferrocyanide and water, and solution C comprises sodium chloride, a surfactant and water.
[0006] In a second aspect, the present application provides a Prussian blue nanomaterial obtained by the preparation method of any embodiment of the present application, wherein the Prussian blue nanomaterial is spherical particles with a particle size of 5-8 μm.
[0007] In a third aspect, the present application provides a preparation method of any embodiment of the present application or an application of the Prussian blue nanomaterial of any embodiment of the present application in a positive electrode material for a battery.
[0008] The Prussian blue nanomaterials and preparation methods and applications thereof provided in various embodiments of the present application divide the raw materials into three independent solutions, solution C contains only sodium chloride and a surfactant, solution A includes an iron source, a chelating agent, a reducing agent and water, the solution B includes sodium ferrocyanide and water, solution A includes an iron source, a chelating agent, a reducing agent and water, the solution B includes sodium ferrocyanide and water, solution A and solution B are added to solution C by dropwise addition, and acid treatment is performed after the reaction. The obtained Prussian blue nanomaterial has the advantages of uniform size and good dispersibility, which is conducive to exerting good rate charge and discharge performance in sodium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] In the drawings, which are not necessarily drawn to scale, the same reference numerals may describe similar parts in different views. The same reference numerals with letter suffixes or different letter suffixes may represent different instances of similar parts. The accompanying drawings generally illustrate various embodiments by way of example and not limitation, and together with the specification and claims, are used to illustrate the embodiments applied for. When appropriate, the same reference numerals are used throughout the drawings to refer to the same or similar parts. Such embodiments are illustrative and are not intended to be exhaustive or exclusive embodiments of the present apparatus or method.
[0010] Figure 1 A field emission scanning electron microscope image of the Prussian blue nanomaterial of Example 1 of the present application is shown; Figure 2 A field emission scanning electron microscope image of the Prussian blue nanomaterial of Example 2 of the present application is shown; Figure 3 A field emission scanning electron microscope image of the Prussian blue nanomaterial of Comparative Example 1 is shown; Figure 4 The X-ray diffraction patterns of the Prussian blue nanomaterials of Example 1, Example 2 and Comparative Example 1 are shown; Figure 5 The charge and discharge curve of the sodium ion battery corresponding to the Prussian blue nanomaterial of Example 1 is shown; Figure 6 The charge and discharge curve of the sodium ion battery corresponding to the Prussian blue nanomaterial of Example 2 is shown; Figure 7 The rate performance curves of the sodium ion batteries corresponding to the Prussian blue nanomaterials of Example 1, Example 2 and Comparative Example 1 are shown. DETAILED DESCRIPTION
[0011] In order to enable those skilled in the art to better understand the technical solution of the present application, the present application is described in detail below in conjunction with the accompanying drawings and specific implementation examples. The embodiments of the present application are further described in detail below in conjunction with the accompanying drawings and specific implementation examples, but are not intended to limit the present application.
[0012] The words "first", "second" and similar words used in this application do not indicate any order, quantity or importance, but are only used to distinguish. The words "include" or "comprise" and similar words mean that the elements before the word include the elements listed after the word, and do not exclude the possibility of including other elements.
[0013] According to an embodiment of the present application, a method for preparing a Prussian blue nanomaterial is provided, characterized in that the preparation method comprises: solution A and solution B are respectively dropped into solution C to obtain a mixed solution, and during the aging process of the mixed solution, a weak acid is added to the aged mixed solution, and after surface treatment, a Prussian blue nanomaterial is obtained, wherein solution A comprises an iron source, a complexing agent, a reducing agent and water, the solution B comprises sodium ferrocyanide and water, and the solution C comprises sodium chloride, a surfactant and water.
[0014] Solution A and solution B are dropped into solution C respectively for reaction. Solution A contains the reaction raw material iron source, and also contains a complexing agent and a reducing agent. Here, the complexing agent reacts with ferrous ions to form a complex, and the reducing agent inhibits the oxidation of ferrous ions.
[0015] Solution B contains the reaction raw material sodium ferrocyanide. After sodium ferrocyanide Na4Fe(CN)6 and divalent iron ions are mixed, a coprecipitation reaction occurs. After subsequent aging, Prussian blue Na2Fe[Fe(CN)6]3 is obtained.
[0016] Adding a surfactant to solution C can improve the dispersibility of the Prussian blue precipitate obtained after the reaction of solution A and solution B.
[0017] The purpose of adding sodium chloride to solution C is to increase the sodium ion concentration in the reaction system and promote the entry of sodium ions into the crystal lattice.
[0018] The agglomeration of the precipitate obtained after the reaction can be effectively reduced by the reaction method of dropping solution A and solution B into solution C.
[0019] The reaction principle is that the iron source first reacts with the complexing agent to obtain a complexing agent-ferrous ion complex, which is then added to solution C to undergo a coprecipitation reaction with sodium ferrocyanide to obtain Na2Fe[Fe(CN)6]3.
[0020] The precipitate formed after aging is treated with weak acid to modify the morphology of the Prussian blue nanomaterial precipitated in the mixed solution. The modified Prussian blue nanomaterial can inhibit the irregular agglomeration of nanoparticles, so that the particle size of the Prussian blue nanomaterial obtained after weak acid treatment is more uniform, and the irregular agglomeration is reduced to a great extent. In the application of sodium ion batteries, the material cycle stability can be enhanced, the discharge specific capacity can be improved, and the rate discharge performance can be optimized.
[0021] In some embodiments, the dripping speed of solution A and solution B into solution C can be 10-30 ml / h respectively; preferably, the dripping speed can be 15-25 ml / h, for example, 18 ml / h. The dripping process can be carried out by a peristaltic pump. Through this suitable dripping speed, the agglomeration phenomenon of the precipitate obtained after the reaction can be effectively reduced.
[0022] In some embodiments, the process of dripping solution A and solution B into solution C, the aging process and the weak acid treatment process are performed at room temperature, that is, harsh reaction conditions are not required.
[0023] In some embodiments, the process of dripping solution A and solution B into solution C is carried out under a protective atmosphere, such as argon, to avoid oxidation during the dripping process.
[0024] In some embodiments, the concentration of the iron salt in the solution A is 0.01 mol / L to 0.1 mol / L; the concentration of the complexing agent is 0.1-0.3 mol / L; and the concentration of the reducing agent is 3-6 g / L.
[0025] In some embodiments, after solution A is prepared, it is allowed to stand for 1-5 hours, so that solution A can be fully complexed during the standing process.
[0026] In some embodiments, the concentration of sodium ferrocyanide in the solution B is 0.01 mol / L ~ 0.1 mol / L.
[0027] In some embodiments, the concentration of sodium chloride in the solution C is 0.1 mol / L to 1 mol / L, and the concentration of the surfactant is 20-40 g / L, so as to achieve a better dispersion effect on the product in the coprecipitation reaction process, thereby achieving a better dispersion effect on the Prussian blue nanomaterial.
[0028] In some embodiments, the volume ratio of solution A, solution B and solution C is 0.5-1.5:0.5-1.5:0.5-1.5; preferably, the volume ratio of solution A, solution B and solution C is 1:1:1, so as to achieve a more suitable ratio of each reaction raw material.
[0029] In some embodiments, the aging time is 5-30 hours, preferably 5-20 hours. The aging process allows the precipitate obtained by the coprecipitation reaction to be more fully converted into Prussian blue nanomaterials.
[0030] In some embodiments, the surface treatment time after adding the weak acid is 30-120 minutes; preferably, the surface treatment time after adding the weak acid is 30-90 minutes. The weak acid treatment time should not be too long or too short, otherwise the surface treatment cannot be fully performed or the effect of better inhibiting agglomeration cannot be achieved.
[0031] In some embodiments, the mass volume ratio of the weak acid to the mixed solution is 0.3-2.4 g:100 ml. The weak acid is an acidic substance that cannot be completely ionized in an aqueous solution. By adding a suitable amount of weak acid, better surface treatment of the product can be performed and the dispersibility of Prussian blue can be improved. If a larger amount is added, the opposite effect may be achieved.
[0032] In some embodiments, the iron source is one or more of ferrous sulfate, ferrous chloride, ferrous citrate, ferrous carbonate, ferrous acetate, and ferrous oxalate.
[0033] In some embodiments, the complexing agent is one or more of citric acid, sodium citrate, sodium pyrophosphate, disodium ethylenediaminetetraacetate, sodium gluconate, sodium acetate, hydroxylamine hydrochloride, and sodium tripolyphosphate.
[0034] In some embodiments, the reducing agent is one or more of ascorbic acid, sodium ascorbate, isoascorbic acid, sodium isoascorbate, and ascorbyl palmitate.
[0035] In some embodiments, the surfactant may be one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, polyoxyethylene fatty acid ester, polyvinyl pyrrolidone, polyvinyl alcohol, and hexadecyltrimethylammonium bromide.
[0036] In some embodiments, the weak acid may be one or more of phosphoric acid, boric acid, formic acid, acetic acid, propionic acid, oxalic acid, malonic acid, adipic acid, and benzoic acid.
[0037] In some embodiments, after the weak acid treatment, the precipitate in the mixed solution is separated, and the precipitate is washed and dried to obtain the Prussian blue nanomaterial. The washing process includes washing with water and washing with anhydrous ethanol, and can be washed with water 3 times and washed with anhydrous ethanol once. The drying temperature is 80-140° C. and the drying time is 10-15 h.
[0038] According to the embodiments of the present application, there is also provided a Prussian blue nanomaterial obtained by the preparation method of any embodiment of the present application, wherein the Prussian blue nanomaterial is spherical particles with a particle size of 5-8 μm.
[0039] According to the embodiments of the present application, a preparation method of any embodiment of the present application or an application of the Prussian blue nanomaterial of any embodiment of the present application in a positive electrode material of a battery is also provided. The Prussian blue nanomaterial synthesized in the present application as a positive electrode material of a sodium ion battery can have a good discharge specific capacity and a good rate discharge performance, which is beneficial to improving the electrochemical performance of the sodium ion battery.
[0040] Example 1 Step 1: Dissolve ferrous chloride, sodium citrate and isoascorbic acid in deionized water to prepare 100 mL of solution A, wherein the concentration of ferrous chloride is 0.03 mol / L, the concentration of sodium citrate is 0.18 mol / L, and the concentration of isoascorbic acid is 5 g / L.
[0041] Step 2: Dissolve sodium ferrocyanide in deionized water to prepare 100 mL of solution B with a concentration of 0.03 mol / L.
[0042] Step 3: Dissolve sodium chloride and polyvinyl pyrrolidone in deionized water to prepare 100 mL of solution C, with a sodium chloride concentration of 0.5 mol / L and a polyvinyl pyrrolidone concentration of 30 g / L.
[0043] Step 4: Under argon protective gas, add solutions A and B dropwise into solution C using a peristaltic pump to obtain a mixed solution at a dropping rate of 18 ml / h.
[0044] Step 5: After the dropwise addition is completed, the reaction vessel is sealed and allowed to stand for aging for 20 hours.
[0045] Step 6: After aging, add 1 ml of concentrated phosphoric acid (mass fraction 85%) to the mixed solution for surface treatment, stir for 30 min, and let stand for 1 h again.
[0046] Step 7: Pour off the supernatant, collect the precipitate, wash it with deionized water and centrifuge it 3 times, wash it with anhydrous ethanol and centrifuge it once, collect the precipitate, and obtain the surface-treated Prussian blue nanomaterial.
[0047] Step 8: Dry the product in a vacuum oven at 100°C for 12 h, grind it, and pass it through a 200-mesh sieve for testing.
[0048] The surface structure of the Prussian blue nanomaterial of Example 1 was observed by field emission scanning electron microscopy (SEM), and the following was obtained: Figure 1 Results shown.
[0049] Example 2 Step 1: Dissolve ferrous chloride, sodium citrate and isoascorbic acid in deionized water to prepare 100 mL of solution A, wherein the concentration of ferrous chloride is 0.03 mol / L, the concentration of sodium citrate is 0.18 mol / L, and the concentration of isoascorbic acid is 5 g / L.
[0050] Step 2: Dissolve sodium ferrocyanide in deionized water to prepare 100 mL of solution B with a concentration of 0.03 mol / L.
[0051] Step 3: Dissolve sodium chloride and polyvinyl pyrrolidone in deionized water to prepare 100 mL of solution C, with a sodium chloride concentration of 0.5 mol / L and a polyvinyl pyrrolidone concentration of 30 g / L.
[0052] Step 4: Under argon protective gas, add solutions A and B dropwise into solution C using a peristaltic pump to obtain a mixed solution at a dropping rate of 18 ml / h.
[0053] Step 5: After the dropwise addition is completed, the reaction vessel is sealed and allowed to stand for aging for 20 hours.
[0054] Step 6: After aging, 1.4 ml of concentrated phosphoric acid (mass fraction 85%) was added to the mixed solution for surface treatment, stirred for 30 min, and allowed to stand for 1 h.
[0055] Step 7: Pour off the supernatant, collect the precipitate, wash it with deionized water and centrifuge it 3 times, wash it with anhydrous ethanol and centrifuge it once, collect the precipitate, and obtain the surface-treated Prussian blue nanomaterial.
[0056] Step 8: Dry the product in a vacuum oven at 100°C for 12 h, grind it, and pass it through a 200-mesh sieve for testing.
[0057] The surface structure of the Prussian blue nanomaterial of Example 2 was observed by field emission scanning electron microscopy (SEM), and the following was obtained: Figure 2 Results shown.
[0058] Comparative Example 1 The preparation method of Prussian blue is the same as steps 1 to 5 of Example 1, and the weak acid surface treatment step is skipped to proceed to the subsequent steps. The surface structure of the Prussian blue nanomaterial of Comparative Example 1 was observed by field emission scanning electron microscopy (SEM), and the following was obtained: Figure 3 Results shown.
[0059] Depend on Figure 1 , Figure 2 and Figure 3 It can be seen that the Prussian blue sample without weak acid surface treatment has serious nanoparticle agglomeration phenomenon, no regular morphology and good dispersibility, while the sample after acid surface treatment is spherical particles with a particle size of 5-8 μm, good dispersion between particles and uniform size.
[0060] The Prussian blue nanomaterials obtained in Example 1, Example 2 and Comparative Example 1 were tested by X-ray diffraction (XRD), and the corresponding XRD spectra of Example 1, Example 2 and Comparative Example 1 were obtained as follows: Figure 4 As shown, through Figure 4 It can be obtained that the Prussian blue nanomaterials obtained in Example 1, Example 2 and Comparative Example 1 have the same material composition Na2Fe[Fe(CN)6]3.
[0061] The Prussian blue nanomaterials of Example 1 and Example 2 were used as positive electrode materials and the metal sodium sheet was used as the negative electrode to assemble a sodium ion battery. The charge and discharge performance of the assembled sodium ion battery was tested, and the following results were obtained: Figure 5 , Figure 6 The results are shown. Figure 5 , Figure 6 It can be obtained that the sodium ion battery using the Prussian blue nanomaterial of Example 1 as the positive electrode material has good charge and discharge performance, and the maximum charge and discharge capacity is about 97 mAh / g.
[0062] The Prussian blue nanomaterials of Example 1, Example 2 and Comparative Example 1 were respectively used as positive electrode materials and the metal sodium sheet was used as the negative electrode to assemble sodium ion batteries. The rate performance of the assembled sodium ion batteries was tested, and the following results were obtained: Figure 7 The results shown. Figure 7 It can be seen that the rate performance of Example 1 and Example 2 is significantly better than that of the untreated Comparative Example 1. The sodium ion batteries corresponding to Example 1 and Example 2 show good capacity performance under large currents (such as 1C, 2C, 5C and 10C) and a large number of cycles.
[0063] In addition, although exemplary embodiments have been described herein, the scope includes any and all embodiments based on the present application with equivalent elements, modifications, omissions, combinations (e.g., various embodiments intersecting schemes), adaptations or changes. The elements in the claims are to be interpreted broadly based on the language adopted in the claims, and are not limited to the examples described in this specification or during the practice of this application, and the examples are to be interpreted as non-exclusive. Therefore, this specification and examples are intended to be considered as examples only, and the true scope and spirit are indicated by the following claims and the full scope of their equivalents.
[0064] The above description is intended to be illustrative rather than restrictive. For example, the above examples (or one or more schemes thereof) may be used in combination with each other. For example, a person of ordinary skill in the art may use other embodiments when reading the above description. In addition, in the above-mentioned specific embodiments, various features may be grouped together to simplify the present application. This should not be interpreted as an intention that a feature of an application that does not require protection is necessary for any claim. On the contrary, the subject matter of the present application may be less than all the features of an embodiment of a particular application. Thus, the following claims are incorporated herein in the specific embodiments as examples or embodiments, wherein each claim is independently a separate embodiment, and it is considered that these embodiments may be combined with each other in various combinations or arrangements. The scope of the present invention should be determined with reference to the appended claims and the full scope of equivalent forms granted by these claims.
[0065] The above embodiments are only exemplary embodiments of the present application and are not intended to limit the present invention. The protection scope of the present invention is defined by the claims. Those skilled in the art may make various modifications or equivalent substitutions to the present invention within the essence and protection scope of the present application, and such modifications or equivalent substitutions shall also be deemed to fall within the protection scope of the present invention.
Claims
1. A method for preparing a Prussian blue nanomaterial, characterized in that: The preparation method comprises: respectively dropping solution A and solution B into solution C to obtain a mixed solution, adding a weak acid to the aged mixed solution during aging, and performing surface treatment to obtain a Prussian blue nano material, wherein solution A comprises an iron source, a complexing agent, a reducing agent and water, solution B comprises sodium ferrocyanide and water, and solution C comprises sodium chloride, a surfactant and water.
2. The preparation method according to claim 1, characterized in that: The dropping speeds of solution A and solution B into solution C are 10-30 ml / h respectively.
3. The preparation method according to claim 1, characterized in that: The aging time is 10-30h.
4. The preparation method according to claim 1, characterized in that: The surface treatment time after adding weak acid is 30-120 minutes.
5. The preparation method according to claim 1, characterized in that: The mass volume ratio of weak acid to mixed solution is 0.3-2.4 g: 100 ml.
6. The preparation method according to claim 1, characterized in that: The concentration of sodium ferrocyanide in the solution B is 0.01 mol / L to 0.1 mol / L.
7. The preparation method according to claim 1, characterized in that: The concentration of sodium chloride in the solution C is 0.2 mol / L to 1 mol / L; the concentration of the surfactant is 20-40 g / L.
8. The preparation method according to claim 1, characterized in that: The concentration of the iron salt in the solution A is 0.01 mol / L to 0.1 mol / L.
9. The Prussian blue nanomaterial obtained by the preparation method according to any one of claims 1 to 8, wherein the Prussian blue nanomaterial is spherical particles with a particle size of 5-8 μm.
10. Use of the preparation method according to any one of claims 1 to 8 or the Prussian blue nanomaterial according to claim 9 in a positive electrode material for a battery.
Citation Information
Patent Citations
Prussian blue material and preparation method thereof
CN110078096A
Prussian blue material, and preparation method and application thereof
CN110921681A
Prussian blue analogue single crystal with three-dimensional ordered interconnected macroporous structure as well as preparation method and application of Prussian blue analogue single crystal
CN117107363A
Prussian blue analogue material and preparation method thereof
CN118359210A